Utilização do indicador custo em risco, na decisão de apreçamento em projetos de alta tecnologia, em leilões reversos e em concorrências de menor preço - Mauad, Luiz Guilherme Azevedo (2010)
Purchasing high quality and low price products has become a consumer fixation, mainly where the lowest price is demanded and in reverses auctions, whether electronic or not. The importance of establishing retail prices of projects, products and services has been increasing. Therefore, it has become a strategic and challenging task for managers while also being one of their great fears. In a global and highly competitive market, price setting may influence consumers buying choices: a product s value and quality, which meet their expectations, will sell a product or project. On the other hand, a price inaccurately fixed may turn offers down and lead a company into unwished results. Research shows that markup pricing method is still the most common technique used by companies. However, fixing a price based on this method and taking into account a deterministic cost value may lead a company into making the wrong decisions and taking unnecessary risks. Prices undergo the influence of several costs and market related factors, which, somehow, have some kind of uncertainty risk. Nevertheless, when one is dealing with costs this uncertainty becomes more latent. Therefore, they must be taken into consideration in the company s pricing process. The present research study, based on RiskMetrics concepts such as VaR and, mainly, CorporateMetrics, proposes and applies a pricing model named Cost at Risk based Price (PCeR) in a high technology venture. The model approaches costs incurred stochastically instead of deterministically and takes into account the risks inherent to their composing parameters. The model has proven to be a useful and flexible tool, which offers to managers greater understanding when fixing retail prices. That understanding may assist organizations to reach a market, overcome their competitors and grow profitably.